Divine teaching and the way of the world a defense of revealed religion - Fleischacker, Samuel (Oxford : Oxford University Press, 2011)
Samuel Fleischacker offers a defense of 'revealed religion' - religions that regard a certain text or teaching as wholly authoritative over one's life. By reconciling it with secular cognitive and moral practices that allow people to work together, he shows how these two worldviews can be brought together.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Religion -- Philosophy; Religion and ethics; Truth -- Religious aspects